A new exact equivalent circuit of the medium voltage three-phase induction motor - Laura Collazo Solar; Angel A. Costa Montiel; Miriam Vilaragut Llanes; Vladimir Sousa Santos; Abel Curbelo Colina (Institute of Advanced Engineering and Science, 2020)
This paper proposes a new equivalent circuit for medium voltage and great power induction motors considering the more complete information given by the manufacturer. A methodology for obtaining the parameters of the equivalent circuit is presented, having this circuit the advantage of allowing the electrical calculation of all the power losses and the realization of the power balance. It is an achievement of this work a new way of calculating and representing the additional losses using a resistance located in the rotor circuit. Then, three types of losses are considered as a part of a power balance: the conventional or joule effect variable losses, the constant losses, and the additional losses. The proposed method is straight and non-iterative. It was applied to a case study motor of 6000 V and 2500 kW located at the Maximo Gomez Power Plant in Cuba.